The Effectiveness of Peer Assessment in Assessing Students' Spiritual Attitudes in Islamic Religious Education Learning in Middle Schools - Fitri, Fitri (Cahaya Ilmu Cendekia Publisher, 2023)
Purpose of the study: To determine the effectiveness of peer assessment in assessing spiritual attitudes in Islamic religious education learning in junior high schools. Methodology: The research method uses a qualitative method with descriptive research type, the research sample is an Islamic religious education teacher in junior high school with research instruments in the form of interviews, research analysis using Mileh and Huberman. Main Findings: Peer assessment in assessing spiritual attitudes is said to be effective because it has run according to its duties and functions in making it easy for teachers to evaluate student learning outcomes and train students so that they have skills when carrying out evaluations. Novelty/Originality of this study: Many studies pay attention to cognitive aspects in assessment or learning, but this research highlights the spiritual dimension.